2006
DOI: 10.1186/1465-9921-7-56
|View full text |Cite
|
Sign up to set email alerts
|

Latent Tuberculosis in HIV positive, diagnosed by the M. Tuberculosis Specific Interferon-γ test

Abstract: Background: Although tuberculosis (TB) is a minor problem in Denmark, severe and complicated cases occur in HIV positive. Since the new M. tuberculosis specific test for latent TB, the QuantiFERON-TB In-Tube test (QFT-IT) became available the patients in our clinic have been screened for the presence of latent TB using the QFT-IT test. We here report the results from the first patients screened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
169
7
11

Year Published

2007
2007
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 192 publications
(199 citation statements)
references
References 30 publications
12
169
7
11
Order By: Relevance
“…The bacillary burden in LTBI is many logs lower than in active disease and so it may not be possible to conclude with confidence that a negative IFNGRA excludes LTBI. In this respect addition of further species-specific antigens to test formulations might incrementally improve sensitivity (29,37). Cutoffs for novel diagnostic tests are often defined by receiver operator characteristic (ROC) analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The bacillary burden in LTBI is many logs lower than in active disease and so it may not be possible to conclude with confidence that a negative IFNGRA excludes LTBI. In this respect addition of further species-specific antigens to test formulations might incrementally improve sensitivity (29,37). Cutoffs for novel diagnostic tests are often defined by receiver operator characteristic (ROC) analysis.…”
Section: Discussionmentioning
confidence: 99%
“…A low sensitivity to the skin tuberculin test will be overcome, in part, by the introduction of two blood tests (T-SPOT.TB and Quantiferon-TB Gold), which are based on the detection of IFN-gamma released by T lymphocytes in response to Mycobacterium tuberculosis-specific antigens. Clinical studies examining these new tests in the HIV patient population are in progress [20].…”
Section: Other Laboratory Assessmentsmentioning
confidence: 99%
“…In studies evaluating T-SPOT.TB and its ELISPOT precommercial version 20,21 or the QFT-G tests, 22,23 in vitro tests obtained higher rates of positive results than TST in diagnosing LTBI, 23,24 and a better association between positive results and presence of risk factors for LTBI. 22,23 In recent years, some studies in HIV-infected populations reported similar sensitivities for both IFN-γ tests.…”
Section: Hiv Infected Patientsmentioning
confidence: 99%